How well do seed production traits correlate with leaf traits, whole-plant traits and plant ecological strategies? - Pierce, Simon; Bottinelli, Arianna; Bassani, Ilaria; Ceriani, Roberta M; Cerabolini, Bruno E. L (Plant ecology, 2014)
The principal axes of variation in plant function include the economics spectrum and size variation, both of which are implicated in primary ecological strategies. However, it is unclear to what extent vegetative traits and primary strategies correlate with reproductive traits, particularly for seed production. Fifteen traits, including whole-plant, leaf and seed traits (mass, number, total mass of seeds, volume and variance), were measured for 371 species from a range of habitats in Italy. Classification of Grime’s competitor, stress-tolerator, ruderal (CSR) strategies was applied from leaf area, leaf dry matter content and specific leaf area data. Relationships between vegetative traits, CSR values and seed traits were determined using principal components analysis (PCA) and Pearson’s correlation coefficients. PCA1 was an axis of economics, significantly correlated (positively) with leaf carbon concentration and S-selection, and (negatively) with leaf nitrogen concentration, flowering period and R-selection, but not seed traits. PCA2 was a plant size axis, significantly positively correlated with canopy height, leaf mass, C-selection and to a lesser extent seed size traits and total mass of seeds. PCA3 was a specific seed size-seed output axis, correlated positively with seed mass and volume, and negatively with seed number and variance. The loading of seed production traits on a general plant size axis alongside C-selection demonstrates that seed production traits are integral to CSR strategies. However, the stronger contribution of seed traits to a specific axis of variability is suggestive of reproductive variability beyond the CSR strategy, as predicted by the twin-filter model.